Rio - Paris: primórdios da publicação da Literatura Brasileira chez Garnier - Granja, Lucia [UNESP] (My University, 2013)
This article brings to light the latest research on the activities of Baptiste-Louis Garnier, French bookseller and publisher established in Rio de Janeiro, in his relations with the French publishing world: methods, procedures, books, authors and publishers. Cultural exchanges between these two systems helped to consolidate the canon of authors and works of Brazilian Literature in the nineteenth century. The study of these relationships can give full account of some information scholars have provided us and contributes to a better understanding of the process of production and circulation of literary works in Brazil.

Este artigo dá notícias de nossas últimas pesquisas sobre as atividades de BaptisteLouis Garnier, livreiro e editor francês estabelecido no Rio de Janeiro, em suas relações com o mundo editorial francês: métodos, procedimentos, livros, autores e editores. As trocas culturais entre esses dois sistemas ajudaram a consolidar o cânone dos autores e obras da Literatura Brasileira no século XIX e o estudo dessas relações poderá detalhar algumas informações que, até hoje, forneceu-nos a história da Literatura Brasileira, contribuindo para um maior conhecimento do processo de produção e circulação de obras literárias no Brasil.
Rio-Paris: beginnings of Brazilian Literature by Garnier’s publishers
Keywords: História do Livro; História literária; Literatura Brasileira; Globalização da cultura; Baptiste-Louis Garnier; Machado de Assis; José de Alencar; History of books; Literary history; Brazilian Literature; Globalization of culture